PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN FLASH CARDS UNTUK ANAK USIA DINI - Zwesty, Ermina Deasya (LPPM STKIP PGRI Bandar Lampung, 2014)
Learning with Flash cards are the amazing way stimulates learning for children. Using flash card is a popular and effective learning technic, especially for preschool children. Flash cards are designed by standard measure for binginners. Using â€œsee and sayâ€ method and matching technic, Flash cards teach basic concept, like color, shape, number, and letter. Even short poetry for children can be taught by using Flash cards. Repeating poetry and matching words and pictures in one learning activity make children to master some flashcards concept as a fun game.This research aims to know real, factual, accurate description about English learning process use flash cards for binginners MY DOLPHIN Christian School Panjang Bandar Lampung. Besides that it is to know How teachers present English learning, especially for English learning method uses flash cards for binginners, the application of flash cards in learning English, the way of English learning application uses flash cards.The research was conducted at MY DOLPhin CHRISTIAN SCHOOL Panjang Bandar Lampung using qualitative research design. The informan in this research was decided purposively, those are 2 teachers, 1 headmaster, and 3 parents. Collecting data tools were interview, observation and documentation. Analize data used Analysis Interactive Model from Miles and Huberman. it was done through collecting data, reducting data, presenting data, and conclusion.The results show that learning English uses flash cards for children under five suitable for research items used, like English learning design uses flash cards for children under five, 3-4 years, It has been done by teachers well and it is suitable for generic menu what government suggested. The results of children learning are written in the children development books.Based on conclusion above, Flash cards can be used students in Indonesia to learn English. So that by using flash cards English can be taught to students biginners easily. Keywords: Flash cards, accurate description, qualitative, standard measure.